El desarrollo de la psicomotricidad en preescolares limitados físico-motores diagnosticados con parálisis cerebral / The development of psychomotor skills in limited physical-motor preschoolers diagnosed with cerebral paralysis - Llilyan Serrano-Hernández; Angel Efrahin Calzado-Lorenzo; Norys Vázquez-Ávila; Nelson de Jesús Estévez-González (Universidad de Camagüey Ignacio Agramonte Loynaz, 2020)
The investigation is carried out by the necessity of replacing the theoretical-methodological inadequacies that limit the development of the psicomotricidad of the scholars limited physical motors diagnosed with cerebral paralysis when preparing them for its future social inclusion. To solve it is problematic it is summed up in the methodology that favors the development of the psicomotricidad that has as distinctive features, the precision of the relationships among the characteristic neurofisiológicas, neuropsicológicas and neurocognitivas and the conception of the categories individuality and integrality like premises to elevate the quality from the attention to the scholars limited physical motors diagnosed with cerebral paralysis, having like base the periodization of the educational attention to these in the classes of Physical Education, starting from the historical-cultural theory and the physical-educational integral focus. It is a topic of current investigation that belongs together with the politics of the continuous improvement of the subsystem of Special Education; their partial application allows to verify its effectiveness in the pedagogic practice by means of the study of cases, the pedagogic test and the approach of specialists.